1989
DOI: 10.1063/1.101910
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast imaging of ultraviolet laser ablation and etching of polymethylmethacrylate

Abstract: Ablation and etching of the surface of polymethylmethacrylate (PMMA) by pulses of 248 nm laser radiation [∼20 ns full width at half maximum (FWHM)] have been probed by pulses of visible laser radiation (596 nm; <1 ns FWHM). The results were recorded photographically. Modification of the surface structure of the polymer is first visible at 12 ns and appears to be complete in about 60 ns. Emerging solid material, preceded by a shock wave which first becomes visible at 60 ns, reaches a maximum in intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 8 publications
2
35
0
2
Order By: Relevance
“…33a. Such darkening upon laser ablation was reported for PMMA and poly(ethylene terephthalate) (PET) by other researchers and assigned to scattering by ejected materials or bubble formation in the irradiated surface upon laser ablation [194,195]. In this time region, the expansion dynamics measured with both internal and surface configurations were quite similar to each other, as shown in Figs.…”
Section: Darkening and Small Expansion At The Early Part Of The Excimsupporting
confidence: 62%
See 1 more Smart Citation
“…33a. Such darkening upon laser ablation was reported for PMMA and poly(ethylene terephthalate) (PET) by other researchers and assigned to scattering by ejected materials or bubble formation in the irradiated surface upon laser ablation [194,195]. In this time region, the expansion dynamics measured with both internal and surface configurations were quite similar to each other, as shown in Figs.…”
Section: Darkening and Small Expansion At The Early Part Of The Excimsupporting
confidence: 62%
“…For example, it has been revealed that cyclic multiphoton absorption and mutual interactions between excited states were brought about, causing rapid temperature elevation of the polymer matrix [93,95,96] and thermal decomposition of the polymer [95,192]. On the other hand, morphological dynamics has been studied mainly with respect to ejection behavior of fragments or plume [94,172,[194][195][196][197]. Of course the ejection dynamics is a reflection of the molecular process, but direct information is not clearly contained in the ejection behavior, since the primary molecular processes are already completed when fragments or plume ejection are brought about.…”
Section: Introductionmentioning
confidence: 99%
“…Similar nanosecond photography was applied to PMMA and polyimide films by Srinivasan et al, reporting that a shock wave was observed at 60 ns and followed by an explosion of fragmented debris. 17 The shock wave was not clearly confirmed in present work, which may be ascribed to differences in experimental conditions. increases.…”
Section: Resultsmentioning
confidence: 49%
“…The deeper structures, cluster of redeposited material that is formed close to the ablated holes, are then removed by ultrasonic cleaner. Laser ablation has primarily been used on PMMA [96]. A disadvantage of the ablation technique is that it can lead to polymer surface property change in comparison with a polymer's bulk properties [97].…”
Section: Direct Machiningmentioning
confidence: 99%